Mutational Analysis of Residues in the Coiled-Coil Domain of Human Immunodeficiency Virus Type 1 Transmembrane Protein gp41 - Weng, Yongkai (American Society for Microbiology, 1998)
The envelope glycoprotein (Env) of human immunodeficiency virus mediates virus entry into cells by undergoing conformational changes that lead to fusion between viral and cellular membranes. A six-helix bundle in gp41, consisting of an interior trimeric coiled-coil core with three exterior helices packed in the grooves (core structure), has been proposed to be part of a fusion-active structure of Env (D. C. Chan, D. Fass, J. M. Berger, and P. S. Kim, Cell 89:263–273, 1997; W. Weissenhorn, A. Dessen, S. C. Harrison, J. J. Skehel, and D. C. Wiley, Nature 387:426–430, 1997; and K. Tan, J. Liu, J. Wang, S. Shen, and M. Lu, Proc. Natl. Acad. Sci. USA 94:12303, 1997). We analyzed the effects of amino acid substitutions of arginine or glutamic acid in residues in the coiled-coil (heptad repeat) domain that line the interface between the helices in the gp41 core structure. We found that mutations of leucine to arginine or glutamic acid in position 556 and of alanine to arginine in position 558 resulted in undetectable levels of Env expression. Seven other mutations in six positions completely abolished fusion activity despite incorporation of the mutant Env into virions and normal gp160 processing. Single-residue substitutions of glutamic acid at position 570 or 577 resulted in the only viable mutants among the 16 mutants studied, although both viable mutants exhibited impaired fusion activity compared to that of the wild type. The glutamic acid 577 mutant was more sensitive than the wild type to inhibition by a gp41 coiled-coil peptide (DP-107) but not to that by another peptide corresponding to the C helix in the gp41 core structure (DP-178). These results provide insight into the gp41 fusion mechanism and suggest that the DP-107 peptide may inhibit fusion by binding to the homologous region in gp41, probably by forming a peptide-gp41 coiled-coil structure.